THE EFFECT OF INTELLECTUAL CAPITAL ON FIRM VALUE MODERATED BY GOOD CORPORATE GOVERNANCE - Nirmala Putri Anjani; Suwarno Suwarno (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This research aims to assess the effect of Intellectual Capital on firm value, along with the mediating role of GCG. The sample consists of banking firms listed on the Indonesia Stock Exchange over the 2022-2024 period. Data were examined using the PLS-SEM approach. The outcome demonstrate that Intellectual Capital has no statistically significant effect on firm value. In addition, GCG is not found to mediate the association among Intellectual Capital and firm value. This research offers significant insights for organizations to enhance governance quality and adopt a more strategic approach to managing intellectual capital in order to foster the development of sustainable corporate value.